Chemo-Mechanical Factors That Limit Cellular Force Generation - Vazquez-Hidalgo, Esteban; Farris, Carly M.; Rowat, Amy C.; Katira, Parag (Frontiers in Physics, 2022)
Cellular traction forces that are dependent on actin-myosin activity are necessary for numerous developmental and physiological processes. As traction force emerges as a promising cancer biomarker there is a growing need to understand force generation in response to chemical and mechanical cues. Our goal is to present a unified modeling framework that integrates actin-myosin activity, substrate stiffness, integrin bond type, and adhesion complex dynamics to explain how force develops under specific conditions. Our simulation results show that substrate stiffness and number of myosin motors contribute to the maximum actin-myosin forces that can be generated but do not solely control the force transmitted by the cells to the surface, i.e. the traction force. The kinetics of the bonds between the cell and the substrate plays an equally important role. Overall, we find that while the cell can generate large actin-myosin forces in individual stress fibers (> 300 pN), the maximum force transmitted to the surface per cell-substrate attachment only reaches a fraction of these values (approx. 50 pN). Traction stress, the sum of forces transferred by all cell-substrate attachments in a unit area, is biphasic or sigmoidal with increasing substrate stiffness depending on the number of active myosin motors generating forces. Finally, we conclude that adhesions < 1μm^2 generate widely variable traction forces and that impulse, the magnitude and duration of a force generating event, is a key limiting factor in traction stress.